Identification and Management of Paroxysmal Sympathetic Hyperactivity After Traumatic Brain Injury - Zheng, Rui-Zhe; Lei, Zhong-Qi; Yang, Run-Ze; Huang, Guo-Hui; Zhang, Guang-Ming (Frontiers in Neurology, 2020)
Abstract Paroxysmal sympathetic hyperactivity (PSH) has predominantly been described after traumatic brain injury (TBI), in which it associated with hyperthermia, hypertension, tachycardia, tachypnea, diaphoresis, dystonia (hypertonia or spasticity), and even motor features such as extensor/flexion posturing. Despite the pathophysiology of PSH not being completely understood, most researchers gradually agree that PSH is driven by the loss of the inhibition of excitation in the sympathetic nervous system without parasympathetic involvement. Recently, advances in the clinical and diagnostic features of PSH in TBI patients have reached a broad clinical consensus in many neurology departments. These advances should provide more unanimous foundation for the systematic research on this clinical syndrome and its clearly management. Clinically, a great deal of attention has been paying to the definition and diagnostic criteria, epidemiology and pathophysiology, symptomatic treatment, and prevention and control of secondary brain injury of PSH in TBI patients. Potential benefits of treatment for PSH may result from the three main goals: eliminating predisposing causes, mitigating excessive sympathetic outflow, and supportive therapy. However, individual pathophysiological differences, therapeutic responses and outcomes, and precision medicine approaches to PSH management are varied and inconsistent between studies. Further, many potential therapeutic drugs might suppress manifestations of PSH in the process of TBI treatment. The purpose of this review is to present current and comprehensive studies of the identification of PSH after TBI in the early stage, and provide a framework for symptomatic management of TBI patients with PSH.